Analisis Pengendalian Persediaan Bahan Baku dengan Metode Material Requirement Planning pada Coffee & Local Food Waroeng Kobar di Surakarta - Tunjung Saputra, Chaidar; Sunarso (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Demand is an aspect that every company must face, with variations in the amount of demand ranging from high to low levels. This variation in demand levels can pose challenges for company management, especially related to the raw material inventory management system. Excessive raw material inventory can result in increased storage costs, while too little inventory has the potential to cause raw material shortages (stockouts). Therefore, efficiency in inventory management is important so that companies can reduce production costs and ensure operational activities run efficiently, so that the company's goal of achieving profits can be achieved. This research seeks to overcome the problem of raw material inventory management by applying the Material Requirement Planning (MRP) method. The data used in this research comes from primary and secondary data, which are collected through observations, interviews, literature studies, and documentation related to the production process and the condition of raw material inventory in the warehouse, with a case study implemented at Waroeng Kobar in Surakarta. The results of the analysis of raw material inventory with the MRP method show differences in results between each method used, where the LFL method results in an inventory cost of Rp 396,000, the EOQ method of Rp 328,650, and the POQ method of Rp 704,175. This shows that the application of the Economic Order Quantity (EOQ) method at Waroeng Kobar, Surakarta, can save costs up to Rp 673,350.